Export of agricultural raw materials, exchange rate and economic growth in Nigeria: an ARDL approach to cointegration - Waziri, Salisu Ibrahim; Mohamed Nor, Norashidah; Mukhtar, Umar; Mukhtar, B. G. (International Institute for Science, Technology & Education, 2017)
This paper investigated the long run cointegration between export of agricultural raw materials, exchange rate and economic growth in Nigeria. An annual time series data was used for the period of 32 years from 1981 to 2013, and Auto Regressive Distributed Lags (ARDL) cointegration approach was employed in achieving the objective of the study. The result revealed that, both short run and long run models were cointegrated. Agricultural raw material export and exchange rate are instatistically and negatively related to GDP with the exception of exchange rate. Therefore, this paper suggested as part of its policy recommendation that, the Federal Republic of Nigeria in line with its transformation agenda should focus more on human capital, infrastructural and agricultural sector development, and not only increase export of agricultural raw materials, but also encourage exportation of processed agricultural products for achieving inclusive economic growth and development.